Effects of re-melting strategies on densification behavior and mechanical properties of selective laser melted AlSi10Mg parts - Chua, Chee Kai (2018)
Effects of re-melting strategy on densities and mechanical properties of AlSi10Mg samples fabricated by selective laser melting (SLM) were investigated. Strategies of same and opposite re-melting routines based on the alternative stripe scanning routine were performed. The densification behaviors of the SLM manufactured AlSi10Mg samples with different strategies were characterized by a solid densitometer. Tensile strength and elongation were also measured and compared with the samples produced with simple stripe strategy. The results show that remelting strategies result in insignificant increase in the densification and slight decrease in ultimate tensile strength of the SLM components. However, great increase in elongation is obtained by remelting. Furthermore, the same or opposite directional re-melting scanning witnesses no significant difference in results.